(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The study of politeness in the intercultural aspect is a complex and multifaceted field that poses several theoretical problems. Politeness, as a social phenomenon, is deeply rooted in cultural norms, values, and beliefs, making it challenging to define and analyze across different cultures.One of the primary theoretical problems is the lack of a universally accepted definition of politeness. Different cultures and languages have distinct concepts of politeness, making it difficult to establish a common understanding of the term. For instance, what is considered polite in one culture may be perceived as impolite or even rude in another.Politeness is often context-dependent, and power dynamics play a significant role in shaping politeness behaviors. However, the complexity of power relationships and contextual factors can make it challenging to identify and analyze politeness strategies. For example, what is considered polite in a formal setting may not be suitable in an informal setting, and vice versa.Studying politeness in the intercultural aspect also poses methodological challenges. Researchers must navigate issues of data collection, sampling, and analysis, taking into account the cultural and linguistic diversity of participants. Moreover, the use of self-reporting methods or observational studies may not capture the nuances of politeness behaviors.The theoretical problems of studying politeness in the intercultural aspect have significant implications for intercultural communication. Misunderstandings or miscommunications about politeness can lead to conflicts, misunderstandings, or even the breakdown of relationships. Therefore, it is essential to develop a deeper understanding of politeness in the intercultural context to facilitate effective communication and collaboration.